Growth aspirations among Norwegian entrepreneurs - Kolvereid, Lars (Journal of Business Venturing, 1992)
While growing new firms receive considerable attention in the literature, most firms are born small to stay small. Microeconomic and stage-of-development theories of growth generally assume that growth is a natural phenomenon that has nothing to do with the entrepreneur's priorities. More recently, this assumption has been questioned by a number of authors. If the decision to start a business is a choice made by the founder, it may also be assumed that the decision to grow the business is a choice made by the entrepreneur. The present research investigates the relationship between the founder's motives to start the business, education, experience, industry, localization, characteristics of the organization and its environment, the firm's history of growth, and the entrepreneur's growth aspirations. The hypotheses are tested using data from 250 Norwegian entrepreneurs in four different counties of Norway who started their businesses in 1986. The entrepreneur's motives to start the business are found to be related to his or her growth aspirations, but this relationship does not appear to be very strong. Significant relationships are also found between education, industry, and a number of organizational variables, including past growth in turnover and past growth in the number of employees, and the entrepreneur's aspirations to grow the firm in the future. However, growth aspirations are not found to be significantly related to experience, sex, location, or the size of the firm as measured by the number of employees. Entrepreneurs who want their firm to grow and intend to hire additional employees seem to have started their businesses to achieve something, more so than other entrepreneurs. They also tend to have a higher level of education than other entrepreneurs. Moreover, entrepreneurs with strong growth aspirations tend to have started manufacturing firms rather than service firms, and their businesses are found to have fewer and more distant customers and a higher number of competitors than other firms. Almost 40% of the respondents answered that they do not want to grow the firm. This percentage is significantly higher for Norway than for a comparable sample of British and New Zealand entrepreneurs, suggesting that the widespread reluctance to grow found in Scandinavian research may be a cultural phenomenon. Future research should attempt to clarify the relationship between growth aspirations and actual growth, and seek to identify the cultural peculiarities that promote growth unwillingness among Scandinavian entrepreneurs.